A method for the assessment of facial hedonic reactions in newborns - Caroline Ayres; Charles F. Ferreira; Juliana R. Bernardi; Thiago B. Marcelino; Vânia N. Hirakata; Clécio H. da Silva; Marcelo Z. Goldani (Elsevier, 2017)
Objective: This study describes a quantitative and qualitative methodology to assess hedonic responses to sweet stimulus in healthy newborns. Methods: A descriptive, cross-sectional, observational study, with healthy newborns (up to 24 h of life), between 37 and 42 gestational weeks, vaginally born and breastfed previously to all tests. The evaluation of the newborns reactions was performed by hedonic facial expression analysis, characterized by facial expressions with rhythmic serial tongue protrusion after neutral or sweet solution intake. Initially, 1 mL of water solution was provided to the newborn, followed by a 1-minute recording. Afterwards, the same amount of 25% sucrose solution was provided, performing a second recording. The concordance between researchers was analyzed by the Bland-Altman statistical method. Results: A total of 100 newborns (n = 49 males, n = 51 females; mean lifetime = 15 h 12 min ± 6 h 29 min) were recorded for neutral and sucrose solution intake, totaling 197 videos (n = 3 missing in the water treatment). These videos were double-blind analyzed and the test revealed a 90% concordance between the two trained researchers, in relation to both solutions. The intraclass correlation coefficient was 0.99 for both solutions, with a significant increase in frequency of hedonic expressions evoked by sucrose solution intake. Conclusions: These results confirm that the proposed method has an efficient power to detect significant differences between neutral and sucrose stimuli. In conclusion, this evaluation method of hedonic facial reactions in newborns reflects the response to a specific taste. Resumo: Objetivo: Descrever quantitativamente e qualitativamente uma metodologia para avaliar as respostas faciais hedônicas, em recém-nascidos saudáveis, ao estímulo doce. Métodos: Trata-se de um estudo descritivo, transversal e observacional, com recém-nascidos saudáveis (com até 24 horas de vida), entre 37-42 semanas gestacionais, nascidos por parto vaginal e alimentados previamente aos testes. A avaliação das reações hedônicas dos recém-nascidos foi considerada pelas expressões faciais com séries rítmicas de protrusões de língua após a ingestão de solução neutra ou doce. Inicialmente, 1 mL de solução neutra (água) foi fornecida para o recém-nascido, seguido de uma filmagem de 1 minuto. Sequencialmente, a mesma quantidade de solução de sacarose 25% foi fornecida, realizando-se uma segunda gravação. A concordância entre os pesquisadores foi analisada pelo método estatístico de Bland-Altman. Resultados: Um total de 100 recém-nascidos (n = 49 do sexo masculino, n = 51 do sexo feminino, tempo de vida média = 15 h 12 min ± 6 h 29 min) foram registrados para a ingestão de solução neutra e de sacarose, totalizando 197 vídeos (n = 3 perdas para o tratamento água). Estes vídeos foram analisados em duplo-cego e o teste revelou uma concordância de 90%, para ambas as soluções, entre os pesquisadores treinados. O coeficiente de correlação intraclasse foi de 0,99 para as duas substâncias, com um aumento significativo nas frequências das expressões faciais hedônicas evocadas pela ingestão de sacarose. Conclusões: Estes resultados confirmam que o método proposto possui poder estatístico eficiente para detectar diferenças entre estímulos neutros e sacarose. Em conclusão, este método de avaliação de reações faciais hedônicas em recém-nascidos reflete a resposta para um gosto específico. Keywords: Newborn, Facial expression, Sucrose, Palavras-chave: Recém-nascido, Expressão facial, Sacarose